(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article describes the regional aspects of the disease, the rational use of health facilities and recreational resources, the impact on the health and longevity of the population perspectives of medical geography; The following tasks were taken into account: study of regional features of health from a medical geographical point of view; Medical geographical analysis and assessment of the natural conditions and economy of some regions; division of the studied area into medical geographical regions, ecological and nosogeographic assessment of the region, etc.